Language Choice and Attitude among Native Lubuklinggau Community - Sastika Seli; Ladie Resyta Arma; Dewi Syafitri (EDULIA: English Education, Linguistic and Art Journal, 2021)
This study aims to explain the choice of language and domains in the Lubuklinggau indigenous people, language attitudes towards the selected language, and the factors determining language choice in the Lubuklinggau indigenous people. The research method used is the descriptive qualitative method. The subjects of this study were the indigenous people of Lubuklinggau. The data collection techniques used in this study were questionnaires and interviews. This study shows three common languages commonly used by the Lubuklinggau indigenous people and seven domains. The three languages are PMLD, BI, and Cul. In conclusion, the Lubuklinggau indigenous people usually use three common languages in seven territories. The choice of language is influenced by several factors such as dominant language, solidarity, prestige and politeness. Keywords: Attitude, Language Choice, Language Domain, Maintenance Multilingualism